Development of Cascade Reactions and Strategies for Carbon Centred Nucleophilic Additions to Blocked Isocyanates - Derasp, Joshua (Université d'Ottawa / University of Ottawa, 2019)
Isocyanates are invaluable bulk chemicals that play a central role in the synthesis of various polymers and provide a key platform for the synthesis of nitrogen-containing molecules such as carbamates and ureas. Unfortunately, isocyanates suffer from high toxicity, low functional group tolerance, and a propensity to undergo deleterious side-reactions. Consequently, blocked (masked) isocyanate derivatives have been the subject of increased interest resulting from their reduced toxicity and exceptional control over isocyanate reactivity. This strategy has largely been relegated to the polymerization literature, although its use in the synthesis of complex urea and carbamate derivatives is well established in synthetic organic chemistry. However, prominent gaps in the blocked isocyanate literature were clear at the outset of this research project. First and foremost, the development of heteroatom-substituted isocyanates, such as N- and O-substituted derivatives, remained relatively scarce despite their potential for the synthesis of important nitrogen-containing derivatives. Furthermore, the additions of carbon-centred nucleophiles on blocked N-, O-, and even C-substituted blocked isocyanates were exceedingly rare. Finally, the use of a blocking group strategy in catalytic transformations of isocyanates remained largely absent from the literature. This was particularly striking given the widespread development of catalytic transformations of isocyanates. As such research efforts began focusing on furthering the development of blocked N-isocyanates as a vital platform for heterocyclic synthesis (chapter 2). Initially, the cascade reactivity of blocked N-iso(thio)cyanates was expanded to incorporate electrophiles such as alkynes (section 2.2). This readily provided access to imidazolone and thiazolidine products. Subsequently, the development of a cascade reaction providing access to 1,2,4-triazin-3(2H)-ones was explored (section 2.3). This provided the first examples of an N-isocyanate cascade which hinged on the use of acid catalysis. Moreover, insight into hydrazone isomerization was gained. Finally, these efforts culminated in the development of cascade reactions providing access to a rare class of 1,2,4-triazinones as well as 5-aminopyridazinones (section 2.4). This provided the first example of a cascade reaction involving a C-C bond formation onto a blocked N-isocyanate derivatives. Furthermore, this development was pivotal in re-focusing attention on the development of general strategies to achieve addition of carbon nucleophiles onto blocked isocyanate derivatives. Towards this end, the development of two strategies to achieve carbon-centred nucleophilic additions on both blocked N- And O-isocyanates were developed (chapter 3). Inspiration from the isocyanate literature led to the development of carboxylic acids as formal carbon nucleophiles (section 3.2). This strategy was found to be quite general for the synthesis of hydroxamates from blocked O-isocyanates. Furthermore, encouraging results were generated on the ability of Grignard reagents to form similar products (section 3.3). Particularly important is the paradigm shift this allows from C-N bond formation to C-C bond formation for the synthesis of hydroxamate derivatives. Furthermore, lead results suggest the potential of this reactivity to translate to blocked N-substituted derivatives, a transformation which had failed with carboxylic acids. Finally, the development of a catalytic amide synthesis from blocked isocyanate precursors was targeted (chapter 4). The use of a blocking group strategy was able to address the current major limitation of isocyanates as amide precursors, that is functional group tolerance (section 4.2). Indeed, a commercially available rhodium catalyst was found to allow efficient amidation of various ambiphilic blocked isocyanate derivatives using arylboroxines as nucleophiles. Mechanistic studies including the use of variable time normalization analysis supported the presence of two alternative kinetic regimes contingent on the reaction conditions employed. Furthermore, these data suggested the success of this transformation, in the case of ambiphilic derivatives, hinged on a rate determining isocyanate release (chapter 4). Finally, initial results strongly support the potential for Boc-carbamates to provide a general platform for amidation in the presence of strong nucleophiles such as primary amines. The potential of a blocking group strategy in catalytic reaction development was further displayed with the development of a palladium catalyzed amidation of blocked derivatives with arylboroxine nucleophiles (section 4.3). Indeed, the use of blocked isocyanates was found to be absolutely key in achieving efficient reactivity with the palladium catalyst. This result, coupled with the sparse reports on blocked isocyanates in catalysis, strongly suggest that the use of such a strategy could allow the development of reactivity otherwise unattainable when using free isocyanates.
Keywords: Blocked isocyanates; Amides; N-isocyanates; O-isocyanates; hydroxamates; hydrazide